Hadith-Based Legal Reasoning on the Beut Bak Kubu Tradition: Contemporary Salafi and Classical Sunni Perspectives - Ahmad Tahrir; M. Chalis; Manan, Abdul; Jailani; Rashidi bin Wahab, Muhammad (South East Asia Regional Intellectual Forum of Qoran Hadith (SEARFIQH), 2026)
This study comprehensively examines the tradition of beut bak kubu in Aceh Besar by focusing on the analysis of the istidlal hadith method according to Contemporary Salafi and Classical Sunni. The main problem raised in this study is the difference in legal perspectives and istidlal methodology between Contemporary Salafi and Classical Sunni. This study uses a descriptive-comparative method to identify the similarities and differences between the theoretical concepts of Contemporary Salafi and Classical Sunni in the “beut bak kubu” tradition. The approach used is a literature study, combined with field studies. The results of the study show that Ahlussunnah wal Jamaah uses a textual approach of tauqifiyyah and the principle of Sadd adz-Dzari'ah, thus viewing this tradition as bid'ah because it is considered to specialize in worship without clear examples. Classical Sunni uses a contextual-accommodative approach with the rules of Al-Adat Muhakkamah and qiyas al-aula from the hadith of date palm stems, thus viewing it as a 'urf sahih that is spiritually and socially beneficial. An analysis of the living hadith reveals that this tradition enlivens the hadith text in cultural behavior, serving as a means of social interaction and education for the ureung beut community. This research objectively maps the differences that arise not in the essence of worship, but rather in the framework of thought (manhajul fikr) regarding the position of space and time within the framework of sharia. Both sides have a logical basis for their arguments, with the common ground being the intention to pray for the safety of those who are buried and the reminder of death (dhikrul maut).